Clearance kinetics of the VGF-derived neuropeptide TLQP-21. (October 2018) - Guo, ZengKui; Sahu, Bhavani S.; He, Rongjun; Finan, Brian; Cero, Cheryl; Verardi, Raffaello; Razzoli, Maria; Veglia, Gianluigi; Di Marchi, Richard D.; Miles, John M.; Bartolomucci, Alessandro
Abstract: TLQP-21 is a multifunctional neuropeptide and a promising new medicinal target for cardiometabolic and neurological diseases. However, to date its clearance kinetics and plasma stability have not been studied. The presence of four arginine residues led us to hypothesize that its half-life is relatively short. Conversely, its biological activities led us to hypothesize that the peptide is still taken up by adipose tissues effectively. [ 125 I]TLQP-21 was i.v. administered in rats followed by chasing the plasma radioactivity and assessing tissue uptake. Plasma stability was measured using LC-MS. In vivo lipolysis was assessed by the palmitate rate of appearance. Results: A small single i.v. dose of [ 125 I]TLQP-21 had a terminal half-life of 110 min with a terminal clearance rate constant, k t, of 0.0063/min, and an initial half-life of 0.97 min with an initial clearance rate constant, k i, of 0.71/min. The total net uptake by adipose tissue accounts for 4.4% of the entire dose equivalent while the liver, pancreas and adrenal gland showed higher uptake. Uptake by the brain was negligible, suggesting that i.v.- injected peptide does not cross the blood-brain-barrier. TLQP-21 sustained isoproterenol-stimulated lipolysis in vivo . Finally, TLQP-21 was rapidly degraded producing several N-terminal and central sequence fragments after 10 and 60 min in plasma in vitro . This study investigated the clearance and stability of TLQP-21 peptide for the first time. While its pro-lipolytic effect supports and extends previous findings, its short half-life and sequential cleavage in the plasma suggest strategies for chemical modifications in order to enhance its stability and therapeutic efficacy. Highlights: i.v.-injected [ 125 I]TLQP-21 had an initial half-life of 0.97 min and a terminal half-life of 110 min. The total net uptake by adipose tissue was 4.4% of the entire i.v.-injected dose equivalent. Upon i.v.-injection, liver, pancreas and adrenal gland showed higher uptake, while uptake by the brain was negligible. TLQP-21 sustained isoproterenol-stimulated lipolysis in vivo . TLQP-21 was rapidly degraded to several N-terminal and central sequence fragments after 10 and 60 min in plasma in vitro .